Modeling the dispersal of polar cod (Boreogadus saida) and saffron cod (Eleginus gracilis) early life stages in the Pacific Arctic using a biophysical transport model. (August 2021) - Vestfals, Cathleen D.; Mueter, Franz J.; Hedstrom, Katherine S.; Laurel, Benjamin J.; Petrik, Colleen M.; Duffy-Anderson, Janet T.; Danielson, Seth L.
Highlights: We developed IBMs to study polar cod and saffron cod growth and dispersal. Growth and dispersal were linked to several global-scale climate indices. We identified potential spawning times and locations for polar cod and saffron cod. Source populations likely come from the northern Bering and southern Chukchi seas. Abstract: Polar cod ( Boreogadus saida ) and saffron cod ( Eleginus gracilis ) are the most abundant and ecologically important forage fishes in the Pacific Arctic marine ecosystem, yet little is known about their spawning locations or the habitats occupied by their early life stages (ELS). We developed a biophysical transport model coupled to a Pan-Arctic hydrodynamic ocean circulation model to identify potential spawning locations and examine connectivity between the northern Bering, Chukchi, and Beaufort seas. We simulated the growth and transport of newly hatched polar cod and saffron cod larvae until the early juvenile stage (to 45 mm in length) using circulation model hindcasts from 2004 to 2015. Analyses identified species-specific differences in dispersal trajectories, despite similar hatch times and locations. Strong interannual variability in growth and dispersal was linked to several global-scale climate indices, suggesting that larval growth and transport may be sensitive to environmental perturbations. Results show that polar cod spawned in the northern Chukchi Sea may be an important source of larvae for the Beaufort Sea and Arctic Basin, while observed larval aggregations in the Chukchi Sea likely originated in the northern Bering and southern Chukchi seas. This study provides new information about potential spawning times and locations for polar cod and saffron cod in the Pacific Arctic and helps to identify important ELS habitat. This knowledge can help improve the management of these species and, by examining how larval connectivity changes in response to changing environmental conditions, improve our ability to anticipate how these species may respond in a rapidly changing Arctic.